Go : design patterns for real-world projects : building production-ready solutions in Go using cutting-edge technology and techniques /: design patterns for real-world projects : building production-ready solutions in Go using cutting-edge technology and techniques. (2017) - Vivien, Vladimir; Castro Contreras, Mario; Ryer, Mat
No abstract available